Comparative Study of the Silver Nanoparticle Synthesis Ability and Antibacterial Activity of the Piper Betle L. and Piper Sarmentosum Roxb. Extracts. (27th May 2021) - Nguyen, Ngoc Hoi; Nhi, Tran Thi Yen; Van Nhi, Ngo Thi; Cuc, Tran Thi Thu; Tuan, Pham Minh; Nguyen, Dai Hai
Abstract : Piper betle ( P. betle ) and Piper sarmentosum ( P. sarmentosum ) are the two members of the Piper genus, have been reported to be rich in phytochemicals and essential oils, which showed strong reducing power, antibacterial, and antifungal activities. P. betle recently has been studied and applied in several commercial products in the antimicrobial respect, meanwhile its relatives, P. sarmentosum has been lesser-known in this field. In this study, the two Piper species— P. betle and P. sarmentosum were studied to compare their ability in silver nanoparticle synthesis and efficacy in antibacterial activity. P. betle and P. sarmentosum were extracted by distilled water at different temperatures and times. Subsequently, their total reducing capacity was determined by DPPH scavenging and Folin-Ciocalteu assays to choose the appropriate extraction conditions. The silver nanoparticle solutions prepared by the extracts of P. betle (Pb.ext) and P. sarmentosum (Ps.ext) were characterized by Dynamic light scattering (DLS), Zeta potential, UV-vis, and Fourier-transform infrared (FTIR) measurements. Finally, the antibacterial activity of the synthesized silver nanoparticle solutions was tested against Escherichia coli using the agar diffusion well–variant method. The Pb.ext showed stronger reducing power with higher total polyphenol content (~125 mg GAE/mL extract) and better DPPH activity (IC50~1.45%). Both the green synthesized silver nanoparticle solutions (Pb.AgNP and Ps.AgNP) performed significantly stronger antibacterial activity on Escherichia coli compared to their initial extracts. Antibacterial tests revealed that Ps.AgNP showed remarkably better growth inhibition activity as compared to Pb.AgNP. This study would contribute useful and important information to the development of antibacterial products based on green synthesized silver nanoparticles fabricated by the extracts of P. betle and P. sarmentosum .